The dualistic model of passion in adapted sport: a double-serial mediation analysis on satisfaction with life - Teixeira, Diogo S. (2021)
Adapted sports practice has increased in recent years, and has now put an additional demand on research to further explore and understand the characteristics of this field of practice. The main aim of this study was to examine the serial mediation effects of motivation and affective activation in relationships between passion and satisfaction with life in adapted sports athletes. The study sample comprised 143 adapted sports athletes (male = 107) aged between 15 and 59 years (M = 29.21; SD = 10.45) enrolled in distinct modalities. Double serial mediation models were developed according to hypothetical associations, and were analyzed using PROCESS macro v. 3.3. In both models, no direct effect between the types of passion and satisfaction with life emerged. However, positive indirect effects through self-determined motivation have emerged in the harmonious and obsessive passion models, as for a distinct and positive effect of relatedness in satisfaction with life